Polycentric Governance of Privately Owned Resources in Circular Economy Systems - Patala, Samuli; Albareda, Laura; Halme, Minna (Journal of Management Studies, 2022)
AbstractNatural resource scarcity is giving rise to new forms of resource governance and so enhancing the transition to more sustainable resource use. One key development is the growth of circular economy systems, where residual resources are reused in closed‐loop systems. This requires an understanding of how diverse actors collectively govern the sustainable use and sharing of privately owned residual and waste resources. Our empirical analysis of three circular economy systems in Finland, the United States and Spain shows how a polycentric form of governance develops through collective action between businesses, the public sector, and societal actors based on multiple units of cooperation. Adopting insights from the polycentric governance of commons, we develop a theory of polycentric governance for privately owned residual resources. Our findings show that polycentric governance involves three main interacting elements: mutual adjustment between actors, practices for collective agency, and structures for sharing resources. As well as contributing to the understanding of collective action for sustainability, these findings also advance the interorganizational governance literature.